Application of a Diatom Transfer Function to Quantitative Paleoclimatic Reconstruction — A Case Study of Yunlong Lake, Southwest China - Zou, Yafei; Wang, Luo; He, Haibo; Liu, Guangxin; Zhang, Jiaoyang; Yan, Yao; Gu, Zhaoyan; Zheng, Hongbo (Frontiers in Earth Science, 2021)
Although diatom records from lake sediments have been used for quantitative paleoclimatic reconstruction, their validity and sensitivity have rarely been tested rigorously. At Yunlong Lake, an alpine lake in Southwest China, we studied the seasonal succession of diatom assemblages to produce a mean surface water temperature (MSWT) transfer function. In addition, based on the spatial distribution of surface diatom assemblages with water depth, we produced a diatom-water depth (WD) transfer function. Combined with the analysis of diatom assemblages in a sediment core (YL2013-A), changes in surface water temperature and water level over the last 100 years were quantitatively reconstructed using the diatom-based transfer functions. Comparison with records of regional meteorology and reservoir water capacity revealed that the diatom-based lake water level reconstruction is a sensitive indicator of short-term fluctuations in precipitation, and it also reflects a long-term stepwise rise in water level caused by the impounding and large-scale extension of the reservoir. In addition, the diatom-inferred MSWT is consistent with the changes in air temperature prior to large-scale human disturbance of the site. However, after the extension of the reservoir, although the regional air temperature continued to increase, the water temperature decreased substantially. This suggests that the large increase in lake water volume in the short term led to a decrease in the average water temperature, which in turn led to the occurrence of a diatom bloom in the cold season. The results demonstrate that diatom transfer functions based on modern observations of the same lake has a high environmental sensitivity and can be used for the quantitative reconstruction of regional climate change. Overall, our findings provide a foundation for the use of lake diatom records for quantitative paleoclimatic reconstruction on various timescales.